BRAND COMMUNICATION STRATEGY OF CV INTI PERSADA IN BUILDING BRAND AWARNESS - Yuni Tresnawati; Anindita, Anindita; Alyssa Edwina Imad Khalid Bakhour; Riatun, Riatun (International Journal of Social Science, 2024)
This research aims to investigate and analyze the Brand Communication Strategy implemented by CV Inti Persada in building Brand Awareness. CV Inti Persada, as the subject of the study, is a company operating in the cleaning services sector, competing with other major cleaning companies. With the increasing competition in the business landscape, understanding how brand communication strategies can influence brand awareness is key to achieving success. The study will discuss fundamental theories related to brand communication and brand awareness. The research approach to be used is qualitative, employing a case study research method and a constructive paradigm.